Генерація анімацій за допомогою штучного інтелекту - Паук, Д. А. (ХНУРЕ, 2025)
This article explores the application of AI technologies in animation, including automatic video generation, frame interpolation, motion capture, and artistic stylization. By leveraging machine learning algorithms, AI enables faster and more cost-effective animation production, reducing the need for extensive manual work. The article highlights AI’s growing role in film production, game development, education, and virtual reality, emphasizing its potential to revolutionize content creation.
Keywords: генерація анімацій; animation